Organizational Justice in Young Churches: Maximizing Fair Treatment of Others and Responding to Violations - Dunaetz, David R. (Jurnal Jaffray, 2020)
Organizational justice is the perception that one is being treated fairly in an organization, especially by those who hold power, such as the leaders within a church, both lay and staff. These perceptions of fairness (or lack of fairness) will influence church members’ commitment to, satisfaction with, and involvement in their church, as well as their psychological and spiritual well-being. Young churches are especially susceptible to the consequences of violations of organizational justice because young churches experience frequent changes in programs and delegation of responsibilities. Leaders of young churches should seek to maximize organizational justice, grounded in biblical principles, in order to have a healthy, functional body of believers who work together to serve God. These leaders need to respond to justice violations with humility, managing any conflicts that occur in effective and constructive ways. They must also work to prevent organizational justice violations in young churches from becoming engrained in the churches’ culture.